On-the-job training, firing costs and employment - Pilar Díaz-Vázquez; Dennis J. Snower (Institute for the Study of Labor (IZA), 2003)
This paper explores the influence of on-the-job training on the employment effect of firing costs. It shows that on-the-job training (generating firm specific skills) causes firing costs to have a contractionary influence on average employment (over the booms and recessions of the business cycle).
Keywords: E24; J64; J23; J24; J32; 330; average employment; firing costs; on-the-job training; Berufsbegleitende Ausbildung; Kündigung; Kosten; Lohnverhandlungstheorie; Beschäftigungseffekt; Konjunktur; Theorie